A review of advances in fatigue and life prediction of fiber-reinforced composites - Wicaksono, Satrio (2013)
This contribution is an attempt to provide a thorough review of past and current research work on fatigue and life prediction of fiber-reinforced composites. In order to summarize and present a comprehensive overview of the current state-of-the-art published works, the reviews in this contribution are broadly summarized into four groups of review; (1) fatigue of fiber-reinforced composites, (2) composite damage mechanism, (3) composite failure criteria and, (4) composite fatigue modeling and life prediction. The review will begin with a discussion of inherent and environmental factors affecting the fatigue of composites. This is followed by a rather extensive description of the composite damage mechanism and a summary of commonly used failure criteria for life prediction. And towards the end, models and methods for fatigue and life prediction of composites are summarized and discussed.